Chronic retinyl palmitate supplementation to middle‐aged Wistar rats disrupts the brain redox homeostasis and induces changes in emotional behavior. Issue 5 (23rd March 2015) - Schnorr, Carlos Eduardo; Bittencourt, Leonardo da Silva; Petiz, Lyvia Lintzmaier; Gelain, Daniel Pens; Zeidán‐Chuliá, Fares; Moreira, José Cláudio Fonseca
<x xml:space="preserve">Abstract</x> Scope Aging process makes older adults especially vulnerable to neurodegeneration and mental disorders. Overconsumption‐related neurotoxic effects of certain dietary nutrients by older population could represent a contribution factor for the development of neuropsychiatric conditions by this subpopulation. Thus, we here investigated whether chronic supplementation with retinyl palmitate, at doses commonly found in vitamin supplements (300, 600, and 3000 mcg of RAE/kg/day), could have an impact on emotional behavior of middle‐aged Wistar rats. Methods and results We report that supplementation with retinyl palmitate for 28 days induces an altered emotional state of middle‐aged Wistar rats and oxidative stress in cerebellum, cerebral cortex, hippocampus, and striatum, associated with imbalance of enzymatic antioxidant defenses, decrease in non‐enzymatic antioxidant defenses, and increase in protein and lipid damages. Conclusion Our data show evidence for (i) changes in emotional reactivity, similar to anxiety, in middle‐aged rats chronically supplemented with retinyl palmitate; and (ii) suggest a possible interrelation between pro‐oxidant events in the brain and these differences in the behavioral profile that cannot be attributed to hepatotoxicity. Our results invite for additional studies to further investigate such interrelation.